Identifikasi faktor resiko utama pada kanker paru non-smoker - Effendy, Lyndia; Pribadi, Florence; Kusumah, Irwin Priyatna; Manurung, Riska Enjelica (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Lung cancer in non-smokers represents a distinct clinical and biological entity from smoking-associated lung cancer, characterized by different risk factors, molecular profiles, and prognosis. Understanding the predominant risk factors in this population is critical for early detection, prevention, and personalized treatment. Purpose: To identify and elucidate the most common risk factor for lung cancer in non-smokers through an integrative review of epidemiological, genetic, and environmental research, highlighting their clinical relevance. Method: The literature review and article search were conducted using the PCC framework (Population, Concept, Context) with sources extracted from three databases: Google Scholar, PubMed, and Scopus. The keywords used included